Forensic analysis of biological evidence : a laboratory guide for serological and DNA typing - McClintock, J. Thomas (Boca Raton : CRC Press, 2014)
'Whether a stand-alone laboratory manual or in conjunction with Richard Li's Forensic Biology, Second Edition, this book provides more than a dozen exercises covering analysis of biological evidence. Originally published as Forensic DNA Analysis: A Laboratory Manual, this greatly revised work offers updated exercises and protocols for all kinds of DNA and serological analyses with delineated objectives, step-by-step procedures, and laboratory supplies including advanced instrumentation. It provides a glossary of terms, 14 general information tables, and ancillary instructor's materials along with background material on DNA, downloadable exercises forms, and video instruction for self-teaching'--
'DNA typing has revolutionized criminal investigations and has become a powerful tool in the identification of individuals in criminal and paternity cases. In the past few years, the general public has become familiar with forensic DNA typing based on exposure from media coverage (e.g., the O.J. Simpson trial, the President Clinton and Monica Lewinsky scandal, and identification of individuals killed in the September 11, 2001 attack on the World Trade Center (WTC) in New York city and the Pentagon in Arlington, VA) and television (e.g., Forensic Files, CSI: Miami). Although these cases have generated widespread media attention, they represent only a small fraction of the thousands of forensic DNA and paternity cases that are conducted by public and private laboratories in the United States and abroad'--
In Process PDAL
Includes bibliographical references (p. 131-132) and index.
Keywords: DNA -- Analysis -- Laboratory manuals; DNA Fingerprinting -- Laboratory Manuals; Forensic genetics -- Laboratory manuals